1990
DOI: 10.1093/clinchem/36.10.1736
|View full text |Cite
|
Sign up to set email alerts
|

1990 Medicare/CLIA final rules for proficiency testing: minimum intralaboratory performance characteristics (CV and bias) needed to pass

Abstract: On March 14, 1990, the Centers for Disease Control and the Health Care Financing Administration published criteria for defining minimum performance in proficiency testing (PT). Using our previously described computer modeling technique, we determined the likelihood of passing PT under the new rules. The model relates combinations of intralaboratory CV and bias to PT performance criteria. For example, a laboratory with a bias of zero and an internal CV of 5% will pass a 10% fixed-limit PT criterion (i.e., the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…All values were within the requested range (SD 0.5 g/dL) of the published proficiency testing program (Clinical Laboratory Improvement Act 1990, Ehrmeyer et al. , 1990).…”
Section: Discussionmentioning
confidence: 60%
“…All values were within the requested range (SD 0.5 g/dL) of the published proficiency testing program (Clinical Laboratory Improvement Act 1990, Ehrmeyer et al. , 1990).…”
Section: Discussionmentioning
confidence: 60%
“…This limit is well within range given by the U.S. Clinical Laboratory Improvement Amendments (CLIA) 1988 guidelines for K + . 20 For Na + , the limit given by the CLIA guidelines is ±4 mmol/L. 15 In spite of taking ± 5 mmol/L as our limit, which is more than the recommended limit, the number of samples showing disagreement were high.…”
Section: Discussionmentioning
confidence: 90%
“…To examine agreement between new and old methods of clinical measurement, Bland and Altman suggested that if the data points encompassed by the mean differences Ϯ 2 SD are not clinically important, then the 2 methods may be used interchangeably. 4 MacIntyre, who demonstrated accuracy of the OPTI 1 for human blood, used the following criteria for further evaluation of interchangeability of instruments, according to the criteria necessary to pass proficiency testing 5 : 80% of data points should be within Ϯ 0.04 pH unit, Ϯ 5 mm Hg of a PCO 2 , and Ϯ 15.51 mm Hg of a PO 2 of a standard analyzer. 2 All the data points of this study encompassed by the mean difference Ϯ 2 SD on the Bland-Altman plots met the criteria defined by MacIntyre (Fig 1A-C).…”
Section: Discussionmentioning
confidence: 99%